Simultaneously improved strength and ductility in a Ce-doped dual-phase Mg–9Li alloy - Zhonghao Heng; Lijuan Huang; Qianwen Zhang; Xianzhe Shi; Jianghua Shen (Journal of Materials Research and Technology)
Rare earth metals are commonly added into Mg–Li alloys for strength or ductility improvement. In this paper, rare earth element Ce was incorporated into a Mg–Li alloy to modify its mechanical properties. It is found that the addition of small amount Ce (0.6 wt%) improves over 13% tensile strengths of the Mg–Li alloy without expense of ductility, owing to the formation of Mg12Ce precipitates. To illustrate the toughening mechanism, an in-situ tensile experiment was performed focusing on crack initiation and fracture behavior at local regions such as phase boundaries. It is found that the deformation incompatibility occurs between the α-Mg and β-Li phases in Mg–9Li, and local strain analysis suggested that the β-Li phase contributes more than the α-Mg phase to the plasticity. However, the incorporation of Ce enhances the deformability of the α-Mg phase by weakening its basal texture, which alleviates the strain incompatibility along the phase boundaries. That is why the strength-ductility dilemma is overcome in the Ce-doped Mg–Li alloy. Besides, microcracks mostly generate within fine strips of α-Mg phase for the Ce-free alloy, while for the Ce-doped alloy both the fine α-Mg phase and precipitate strips serve as crack initiators.